The Kenosis Of Jesus Christ: Model Of The Christian Life According To Philippians 2:5-11 - Ramarolahy Patricia Josette; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR) Publisher, 2024)
In the ancient city of Philippi, resonant with echoes of a bygone prosperity, the apostle Paul wove an indelible narrative in his epistle to the Philippians. Penned during his Roman imprisonment, this literary masterpiece, nestled within the realm of captivity epistles, expresses gratitude to a church intimately entwined with Paul's challenges. At its core lies a profound theme—the